Sub-arc collimator angle optimization based on the conformity index heatmap for VMAT planning of multiple brain metastases SRS treatments - Shen, Jiuling; Dai, Zhitao; Yu, Jing; Yuan, Qingqing; Kang, Kailian; Chen, Cheng; Liu, Hui; Xie, Conghua; Wang, Xiaoyong (Frontiers in Oncology, 2022)
Objective: To investigate the impact of collimator angle optimization in single-isocenter coplanar volume modulated arc therapy (VMAT) stereotactic radiosurgery (SRS) for multiple metastases with respect to dosimetric quality and treatment delivery efficiency. In particular, this is achieved by a novel algorithm of sub-arc collimator angle optimization (SACAO). Methods: Twenty patients with multiple brain metastases were retrospectively included in this study. A multi-leaf collimator (MLC) conformity index (MCI) that is defined as the ratio of area of target projection in beam's eye view (BEV) and the related area fitted by MLC was applied. And accordingly, for each control point, 180 MCI values were calculated with a collimator angle interval of 1 degree. A two-dimensional heatmap of MCI as a function of control point and collimator angle for each full arc was generated. The optimal segmentation of sub-arcs was achieved by avoiding the worst MCI at each control point. Then the optimal collimator angle for each sub-arc would be determined by maximizing the summation of MCI. Each patient was scheduled to undergo single-center coplanar VMAT SRS based on either the novel SACAO algorithm or the conventional VMAT with static collimator angle (ST-VMAT). The dosimetric parameters, field sizes, and the monitoring units (MUs) were evaluated. Results: The mean dose-volumetric parameters for target volume of SACAO were comparable to ST-VMAT while the conformity index (CI), homogeneity index (HI) and gradient index were reduced by SACAO. Improved sparing of organs at risk (OARs) was also obtained by SACAO. Particularly, the SACAO method significantly ($p<0.01$) reduced the field size (76.59± 32.55 vs. 131.95±56.71 cm2) and MUs (655.35±71.99 vs. 729.85±73.52) by 41.11% and 9.54%, respectively. Conclusions: SACAO method could be superior in improving the CI, HI and GI of the targets as well as normal tissue sparing for multiple brain metastases SRS. In particular, SACAO has the potential of increasing treatment efficiency in terms of field size and MU.